2021
DOI: 10.17083/ijsg.v8i3.462
|View full text |Cite
|
Sign up to set email alerts
|

Flow Experience and Situational Interest in Game-Based Learning: Cousins or Identical Twins

Abstract: While game-based learning seems to be an effective instructional approach, the underlying learning and engagement mechanisms of games are still poorly understood. In the current study, we investigated to what extent flow experience and situational interest are different indicators of engagement in game-based learning. Fifty-two Finnish 5th graders played a game on fractions at home during COVID-19 enforced distance learning. Flow and situational interest measures were embedded directly into the game environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 66 publications
2
25
0
1
Order By: Relevance
“…Second, we examined relations between flow experience, situational interest, and epistemic emotions. We expected to find a strong positive correlation between flow and situational interest, as demonstrated in [9]. The downside of correlational analyses is that it only looks for coupling between variables regardless of their magnitude.…”
Section: Present Studymentioning
confidence: 86%
See 2 more Smart Citations
“…Second, we examined relations between flow experience, situational interest, and epistemic emotions. We expected to find a strong positive correlation between flow and situational interest, as demonstrated in [9]. The downside of correlational analyses is that it only looks for coupling between variables regardless of their magnitude.…”
Section: Present Studymentioning
confidence: 86%
“…Situational interest emerges from interaction with the features built into the environment, for example, game elements and game mechanics in learning games. According to Kiili et al [9] flow experience and situational interest can be used as proxies of engagement in game-based learning as these constructs explain why people engage in activities. Their study revealed that although flow experience and situational interest are strongly related, situational interest is mainly related to immersive aspects of flow and does not reflect the fluency dimension of flow.…”
Section: Flow and Situational Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Le Mans Université, EA 4023, LIUM, 72085 Le Mans, France, {iza.marfisi, ludovic.hamon, pierre.laforcade}@univ-lemans.fr 2 Open University of the Netherlands, Heerlen, The Netherlands, roland.klemke@ou.nl 3 Università degli Studi di Genova, franz@elios.unige.it…”
Section: Introduction To the Special Issue On Gala Conf 2020unclassified
“…"Flow Experience and Situational Interest in Game-Based Learning: Cousins or Identical Twins", by Kiili et al [3], investigated to what extent flow experience and situational interest are different indicators of engagement in game-based learning. Experimental results with Finnish 5th graders revealed that, although flow was not related to learning gains, it seems to be a more competence-oriented construct than situational interest as it was positively correlated with in-game performance.…”
Section: Introduction To the Special Issue On Gala Conf 2020mentioning
confidence: 99%